Use of GIS for optimizing a collecting mission for a rare wild pepper (Capsicum flexuosum Sendtn.) in Paraguay - Jarvis, Andy; Williams, K; Guarino, Luigi; Caballero, PJ; Mottram, G (Springer, 2005)
This paper presents an effective method for prioritizing areas within a country for acquisition of germplasm of a crop gene pool for ex situ conservation. The method was applied to the rare wild pepper species, Capsicum flexuosum Sendtn., in south-east Paraguay. A model to prioritize areas for collecting germplasm was constructed by combining (1) a prediction of the species' geographic distribution based on the climate at previous collection points, (2) the distribution of forest margins (the species' natural habitat) and (3) areas accessible by road. The model was then tested in the field by visiting 20 sites having both high and low predicted probability of occurrence of C. flexuosum. Six new populations were found, representing a significant improvement over two previous collecting missions for the species in the same region, undertaken without the use of GIS targeting. Using the most optimistic analysis of model performance, C. flexuosum was found at five out of seven points predicted to harbour the species and not found at four of five points predicted not to harbour the species. The model was then improved by the use of higher resolution climate surfaces. It is recommended that future explorers use more recent and higher resolution satellite images to locate suitable habitats. The method is replicable for different species in different geographic regions and is offered as a means of optimizing efficiency in financially constrained, national plant genetic resources programs.